(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The influence of phenol additions on the composition and lyophilyc properties of the surfactant-rich phases of the non-ionic surfactant Triton X-100 formed at cloud point temperature was investigated.